Is informality a barrier to financial development? - Ceyhun Elgin; Burak R. Uras (SERIEs - Journal of the Spanish Economic Association, 2013)
This study investigates the relationship between financial development and the size of the informal economy. We build a model in which an exogenous variation in the size of the informal sector creates two effects on financial development. Specifically, informal sector harms financial development through increasing financial repression due to tax evasion. However, on the other hand, increasing informal sector size facilitates financial development through easing the capacity constraint on the financial sector. Using a cross-country panel data set of 152 countries over the period 1999-2007 we also provide empirical support for the mechanism of our theory.
Keywords: E02; G28; H59; 330; financial development; informal sector; Finanzsektor; Informelle Wirtschaft; Panel; Welt